SISTEM DIAGNOSIS HAMA DAN PENYAKIT TANAMAN BAYAM BERBASIS ANDROID DENGAN METODE TEOREMA BAYES - Beta Setiawan; Chamdan Mashuri; Mahrus Ali (Fakultas Teknologi Informasi, 2025)
Spinach or amaranthus is a type of green plant commonly consumed by the public and has a long history as a highly nutritious food. Typically, this plant only exhibits mild symptoms of pests and diseases during early stages, which are often overlooked by farmers as common occurrences during the growing season. However, when these symptoms escalate and spread extensively, it is often too late to control them, resulting in decreased productivity or even crop failure. In addressing this issue, an Android-based application system has been developed to identify diseases in spinach plants. The choice of an Androidbased application was due to its cost and time efficiency. Based on conducted research, the author designed a system utilizing the Bayes' Theorem method for diagnosing diseases in spinach plants. This system is capable of providing rapid diagnosis results, including certainty percentages and recommended treatment solutions. Keywords: spinach plant diseases, Expert System, Bayes' Theorem, Android.